SUSTAINABLE AGRICULTURE THROUGH VERTICAL CULTIVATION IN THE GREEN ECONOMY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article explores the intersection of sustainable agriculture and the green economy, with a specific focus on vertical cultivation methods. Vertical farming is a revolutionary approach that leverages advanced technologies and innovative design to maximize plant breeding in limited space while minimizing environmental impact. This scientific work delves into the various facets of this concept, including its environmental benefits, resource efficiency, and potential to address the challenges posed by conventional agriculture. It also highlights the economic opportunities associated with vertical farming, such as job creation and the cultivation of high-value crops. Ultimately, this theme underscores the critical role that vertical cultivation plays in reshaping agriculture for a more sustainable and environmentally conscious future, where food production is both efficient and eco-friendly.